PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PADA BANK GO-PUBLIC DI BEI TAHUN 2014-2018 - Effrita Ayuningtyas; Kartika Hendra Titisari; Siti Nurlaela (INVENTORY: JURNAL AKUNTANSI, 2020)
In order to create maximum company performance, the company must pay close attention to the performance conditions of the company by pressing management to obtain optimal results. This study aims to examine the influence of independent commissioners (X1), audit committees (X2), managerial ownership (X3), board of directors (X4) on company performance (Y). Using the method of multiple linear regression analysis. Sampling with purposive sampling obtained 135 research samples from 27 companies at the Go-Public Bank on the Stock Exchange in 2014-2018. This type of research includes quantitative data. It was found that the independent board of commissioners, audit committee and managerial ownership had no effect on the company's performance. Only the board of directors can influence the company's performance.Keywords: Corporate Governance, Company Performance